Wohneigentumsförderung: Analysen aus räumlicher Perspektive - Alexander Daminger (WISTA – Wirtschaft und Statistik, 2023)
Der Beitrag fasst die wesentlichen Erkenntnisse der kumulativen Dissertation “On the Effects of Homeownership Subsidies on the Spatial Distribution of Population, Housing, and Housing Prices within German Cities and Regions” zusammen, die sich in drei Kapiteln mit den räumlichen Auswirkungen der Wohneigentumsförderung befasst. Das erste Kapitel beleuchtet die Effekte des Förderprogramms ,,Eigenheimzulage“ (1996 bis 2005) auf die räumliche Verteilung der Bevölkerung innerhalb von deutschen Städten. Das zweite Kapitel betrachtet die Thematik aus einer intraregionalen Perspektive. Das dritte Kapitel zeigt anhand der Analyse des ,,Baukindergelds“ (2018 bis 2020) die zu diesen Wanderungseffekten korrespondierenden Preiseffekte auf städtische Mietwohnmärkte. – – This article provides an overview of the key findings from the cumulative dissertation titled "On the Effects of Homeownership Subsidies on the Spatial Distribution of Population, Housing, and Housing Prices within German Cities and Regions”, which explores the spatial impacts of homeownership subsidies over three chapters. Chapter one investigates the effects of the home ownership allowance (“Eigenheimzulage”) (1996-2005) on population distribution within German cities. Chapter two considers the issue from an intraregional perspective. Chapter three demonstrates the price effects on urban rental markets corresponding to these migration effects on the basis of the analysis of the family housing grant (“Baukindergeld”) (2018-2020), which aimed to help families with children buy or build owner-occupied housing.
Keywords: 519; Wohneigentumsquote; Wohnungspolitik; Suburbanisierung; Stadtflucht; Eigenheimzulage; Baukindergeld; homeownership rate; housing policy; suburbanisation; urban flight; home ownership allowance; family housing grant